Spectroelectrochemical Characterization of 1,2-Dipalmitoyl- sn-glycero-3-cytidine Diphosphate Nucleolipid Monolayer Supported on Gold (111) Electrode - Alvarez-Malmagro, Julia (Langmuir : the ACS journal of surfaces and colloids, 2019)
The effect of the electrode potential on the orientation and conformation of the 1,2-dipalmitoyl- sn-glycero-3-cytidine monolayer deposited on a gold (111) electrode surface was described. The potential of zero free charge ( Epzc) for the monolayer-covered electrode was determined to be -0.2 V vs SCE. The differential capacitance and charge density data indicated that the monolayer is stable at the electrode surface when ( E - Epzc) > 0.0 V. At negative rational potentials, a progressive detachment (electrodewetting) of the monolayer occurs. The monolayer is fully detached from the electrode surface at ( E - Epzc) < -0.6 V. The conformation and orientation of the acyl chains and the orientation of the cytosine moiety were determined with the help of photon polarization modulation infrared reflection absorption spectroscopy (PM-IRRAS). The IR measurements demonstrate that the acyl chains are predominantly in the gel phase in the adsorbed state and tilted at an angle of ∼30° with respect to the electrode surface normal. The tilt angle of the acyl chains increases when the film is detached from the gold surface, indicating that the monolayer becomes more disordered. At ( E - Epzc) > 0.0 V, the plane of the cytosine moiety assumes a small angle of ∼20° with respect to the surface. At negative potentials, the tilt angle of the cytosine fragment increases and rotates. With the help of DFT calculations, these changes were explained by the repulsion of the positive pole of the cytosine permanent dipole moment by the positively charged gold surface and its attraction to the metal surface at negative electrode potentials. This work provides unique information for the future development of sensors based on the molecular recognition of nucleoside targets